The Sources of Measured US Agricultural Productivity Growth: Weather, Technological Change, and Adaptation. Issue 4 (5th May 2020) - Chambers, Robert G.; Pieralli, Simone
Abstract : The interaction between US state‐level TFP growth and weather is investigated using growth‐accounting techniques. The focus is on examining how that interaction changed between the 1960s and the end of the twentieth century. An empirical approximation to the production frontier constructed using state‐level data and mathematical programming techniques is used to decompose observed state‐level agricultural TFP growth into four components: technical change, weather‐related shifts in the frontier, input/scale effects, and adaptation to the frontier. Technical change and adaptation to the frontier play a significant role in determining average state total factor productivity. Weather‐related effects differ across Climate‐Hub Regions but are of particular importance in the Midwest.